Penerapan Education Management Information System (Emis) Sebagai Sistem Informasi Manajemen Pada Madrasah Tsanawiyah - Sri Luktafiani (Institusi Agama Islam Negeri (IAIN) Bone, 2024)
The aim of this research is to determine the application of EMIS as a management information system at MTS Bulu-bulu, Tonra District. This research applies qualitative research with a phenomenological approach. Data was obtained by interviewing school operators and teachers at MTS Bulu-bulu, Tonra District, as well as through research and documentation. The data source consists of primary and secondary data. Next, this research involves analysis stages, namely data reduction, data display, and concluding. The results of this research indicate that MTS Bulu-bulu, Tonra District has implemented EMIS in its management information system, including: 1). EMIS; 2). functions and benefits of EMIS in MTS Bulu-bulu, Tonra District; 3). challenges of implementing EMIS in MTS Bulu-bulu, Tonra District. Conclusions based on the implementation of EMIS in MTS Bulu-bulu, Tonra District, it is considered successful, providing benefits for all parties involved.